A framework for analysing research types and practices - Czerniewicz, Laura; Kell, Cathy (Proceedings of the International Conference on Networked Learning, 2014)
In this paper we present a framework for examining the changes that are taking place in the research communication practices of academics from four Southern African universities in the wider context of global moves towards open access. We argue that changes in research activity in higher education systems globally, accompanied by the communicative affordances offered by web 2.0 technologies, are having effects on the ways in which scholars are communicating their research. We assess the extent of change on the scholars in the four universities, drawing on data from the Scholarly Communication in Africa Programme (SCAP) in which 23 academics were interviewed about three recent pieces of research. We therefore developed an overview of 70 pieces of research work, from scholars working in universities in Botswana, Namibia, Mauritius and South African. Traditionally scholars have focused on communicating their research through journal articles or monographs and current rewards and incentives systems at universities continue to emphasise this form of scholar-to-scholar communication. However, growing numbers of academics now communicate their work to governments, to industry and to civil society. Developing a systematic picture of the changing practices of scholars in communicating their work is not easy, given the variety of research projects undertaken across disciplines and contexts. Our framework starts off with identifying five types of research projects, which cut across disciplines and the pure/applied distinction. We then examine these in the light of the scholarly communication cycle and its six stages of conceptualization, data collection and analysis, articulation of findings, and translation and engagement. At each stage we argue the importance of considering social relations, audiences and genres. Finally, we consider these along a continuum of degrees of openness.